Porcentajes de aceite de fritura e hidróxido de potasio en la saponificación de grasas para la obtención de jabón líquido - Perero Vera, Luis Miguel (2017)
The objective of this research was to determine the appropiate percentages of oil and potassium hydroxide to obtain the ideal alkalinity of a liquid soap, using cooking oil as a raw material, in compliance with the requirements for liquid soap of the Ecuadorian technical standard according to the INEN 0842 content. An ANOVA (DCA) AxB was used, with three replicas; The factors under study were: A: Percentage of potassium hydroxide (5 %, 6 % and 7 %) and B: Percentage of cooking oil (25 %, 30 % and 35 %). On the other hand, The variables analized were free alkalinity (AL), alcohol insoluble matter (MIA), chlorides (C), total fat (GT), foam level (NE) and pH. The results showed significant differences (p <0.05) for each of the factors studied as well as their interaction. With the results obtained in the IBM SPSS statistical program, it was possible to establish that the best treatments were T1 ( 25% of oil with 5 % of potassium hydroxide), it also showed GT which had a value of 11.17 %; T3 (25 % oil and 7 % potassium hydroxide) and has a lower alkalinity, additional to that the foam level of T3 is the highest with a value of 67 cm3, T9 (35 % oil with 7 % hydroxide Potassium) obtained the lowest percentage of chlorides (0.19 %), so it expresses that the factors studied had a positive influence on the response variable. It is concluded that T1, T3 and T9 meet most of the requirements of the INEN 842 standard.